Phytochemical Examination and Hepatoprotective Impact of Stem Bark of Oroxylum indicum (L) Vent. on Carbon Tetrachloride Induced Hepatotoxicity in Rat - NandaTripathy, Bichitra; Panda, S. K.; Sahoo, S.; Mishra, S. K.; Nayak, L. (Technological Innovation in Pharmaceutical Research Vol. 3, 2021)
The study is being carried out to screen and evaluate the hepatoprotective activity of Oroxylum indicum bark extracts (L.)Petroleum ether, chloroform, methanolic, and aqueous extracts of O. indicum were tested for hepatoprotective activity against carbon tetrachloride-induced liver damage in mice using silymarin as a control.The phytochemical content of the extracts was determined. The enzyme activities of SGOT, SGPT, and ALP (Serum Glutamate Oxaloacetate Transaminase, Serum Glutamate Pyruvate Transaminase, and Alkaline Phosphatase) were investigated. Alcoholi bark extracts of O. indicum showed activity as compared to carbon tetrachloride therapy. The findings of this study support the conventional use of this plant as a possible hepatoprotective agent.One-way measurement of variance (ANOVA) was used in the statistical analysis, followed by Dunnet's t-test. P-values less than 0.05 were considered significant.